Pengaruh Pernikahan Dini terhadap Pendidikan Anak di Dusun Peropok Kelurahan Semayan Lombok Tengah - Umami, Satria; Wulandari, Aini Husnida (YASIN, 2023)
The purpose of this study is to scientifically reveal the influence of early marriage on children's education in Peropok Hamlet, Semayan Village, Central Lombok. The focus of this research includes; Factors causing early marriage to children's education. This study uses a type of qualitative research and a case study approach. The qualitative method is a research method that reveals certain social situations by correctly describing reality which tries to reveal how early marriage influences children's education in Peropok Hamlet, Semayan Village. To obtain accurate data in this study the authors used data collection methods through questionnaires, observation and documentation. Sources of respondents who were considered competent in providing data for this study were the Head of Peropok Village, children or mothers who had early marriages in Peropok Hamlet, Semayan Village, Central Lombok, totaling 25 people. The results showed that there was an effect of early marriage on children's education. This is based on the results found that the occurrence of early marriage on children's education was found to be 15.5% and the rest was influenced by other factors. or it can be said that there is significant influence and early marriage on children's education in Peropok Hamlet, Semayan Village, Central Lombok.